Відновлення кондиційності баз даних для корекції моделей розподілів вмістів мікроелементів у природних водах - Жуков, М.Н.; Клипа, А.В. (Геоінформатика, 2014)
Продемонстровано метод відновлення гідрохімічних даних на основі логарифмічної моделі кореляційного зв’язку для розв’язання задачі моделювання розподілів вмісту мікроелементів у природних водних об’єктах Полтавської області. На підставі наявної інформації відновлено вміст сухого залишку та розраховано реальний вміст мікроелементів у досліджуваному об’єкті. Доведено дієвість методу та його ефективність, яка залежить від коефіцієнта кореляції між логарифмами досліджуваних значень. Застосування методу дало можливість повноцінно провести запланований експеримент і отримати реальні оцінки інтегральних характеристик екологічного стану природних вод Полтавщини. Для автоматизованих розрахунків розроблено програмний модуль, який може бути рекомендований для застосування в аналогічних ситуаціях. Представлен метод восстановления гидрохимических данных на основе логарифмической модели корреляционной связи для решения задачи моделирования распределений содержания микроэлементов в природных водных объектах Полтавской области. На основе имеющейся информации восстановлено содержание сухого остатка и рассчитано реальное содержание микроэлементов в исследуемом объекте. Доказаны дееспособность метода и его эффективность, которая зависит от коэффициента корреляции между логарифмами исследуемых значений. Применение метода позволило полноценно провести запланированный эксперимент и получить реальные оценки интегральных характеристик экологического состояния природных вод Полтавщины. Для автоматизированных расчетов разработан программный модуль, который может быть рекомендован для применения в аналогичных ситуациях. Purpose. The purpose of the article is to carry out environmental monitoring of natural waters, based on probabilistic methods and statistical modeling of content distribution of chemical elements in water; to recover hydrochemical database quality to correct the model of content distribution of chemical elements in natural waters.
Design/methodology/approach. We used method of probabilistic and statistical analysis to determine patterns of chemical elements behavior in natural waters and evaluate their characteristics of distribution; mathematical modeling for automated construction of parametric density estimates; methods of correlation and regression analysis to establish the relationship between the components of the chemical composition of natural waters and to calculate integral characteristics of ecological condition. Distribution modeling, calculation of statistical characteristics and database quality recovery were performed using MathCad software package.
Findings. The proposed composite model adequately describes the distribution of chemical elements in natural waters in areas with different natural and technogenic conditions. It allows full environmental monitoring of natural water bodies by integrating the density distributions. The quality recovery method of hydrochemical database allowed to calculate the actual content of trace elements in the water, fully carry out the planned experiment and get a real assessment of changes in the ecological condition of the objects.
Practical value/implications. The developed software can be used to assess the ecological state of water not only in the Poltava region, but also in other areas, and can significantly increase the reliability and accuracy of the estimates, which a complete modern environmental monitoring requires. The mathematical module of database quality recovery may also be used to solve such kind of problems.